Characterization of solid lipid nanoparticles produced with carnauba wax for rosmarinic acid oral delivery - Madureira, Ana Raquel (2015)
In the last decade, research studies have increased on the development of delivery systems for polyphenols, for protection, improvement of stability and increase of their bioavailability. Rosmarinic acid is a polyphenol with described bioactivities, such as antioxidant, anti-mutagenic, anti-bacterial and anti-viral capabilities. Thus, the aim of this research work was to produce stable solid lipid nanoparticles (SLN) using carnauba wax as lipidic matrix, for delivery of rosmarinic acid, to be further incorporated into food matrices. Hence, different concentrations of wax (0.5, 1 and 1.5%, w/v) and percentages of surfactant (1, 2 and 3%, v/v) were tested. Physical properties, surface morphology and association efficiencies were studied at time of production and after 28 day at refrigerated storage. Thermal properties and the nature of the chemical interactions between the lipids waxes and rosmarinic acid were also evaluated. The particles showed range size between 35-927 nm and zeta potentials of ca. -38 to 40, showing high stability, with no risk of aggregation due to electric repulsion of SLN. High association efficiencies % (ca. 99%) were obtained. FTIR analyses proved the association of rosmarinic acid and lipidic matrix. The low lipid and high surfactant concentrations leads to small SLN. The surfactant, polysorbate 80 decreases the interfacial tension in the SLN surfaces, preventing aggregation, leading to the development of small particles. These properties were maintained throughout the 28 day of refrigerated storage, and no rosmarinic acid was released by the particles during refrigeration, indicating good compatibility between rosmarinic acid and the waxy core of SLN. The optimum range values to obtain the desirable features for incorporation in a functional food suggest formulations containing 1.0 and 1.5% (w/v) of lipid and 2% (v/v) of surfactant.